Executing US soldiers in England, world war II. Command influence and sexual racism - Lilly, J. Robert (The British journal of criminology, 1997)
Current capital punishment literature is overwhelmingly concerned with civilian executions. Overlooked is capital punishment by the non-civilian sector - the military. This paper researches US executions of soldiers during World War II in England. We conclude that racism exists in the process, but can only be understood through the context of its use. The Visiting Forces Act of 1942 permitted the American military to use capital punishment in England as a disciplinary tool to control a perceived danger: African-American troops socializing with British females, and the potential explosive violence between Caucasian and African-American troops